Effect Of Muscle Energy Technique And Microwave Diathermy On Pain Due To Non-Specific Low Back Pain - Tang, Aco; Haruju, Darmawati; Ramba, Yonathan; Dwiya Lestari, Virny; Ronny, Ronny; Andi Munawarah Abduh, Hardianty (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Non-specific low back pain (NSLBP) can cause pain, muscle imbalances, spasms, and postural alterations. It may also restrict lumbar mobility, compromise the stability of lower back and abdominal muscles, and potentially lead to disability. The application of Muscle Energy Technique (MET) combined with Microwave Diathermy (MWD) has been shown to effectively address these issues by reducing pain, improving muscle balance, relieving spasms, and restoring lumbar mobility. This combination therapy enhances the stability of the core muscles, thereby preventing further disability and improving patient outcomes. This study aimed to investigate the effect of MET combined with MWD on reducing pain in patients with NSLBP at Tadjuddin Chalid Hospital, Makassar. A quasi-experimental design with two groups and pre-test/post-test measurements was used. The study population comprised 21 individuals diagnosed with NSLBP. Using purposive sampling based on specific inclusion criteria and the Slovin formula, a total sample of 20 participants was selected. One individual was excluded for not meeting the criteria. Participants were randomly assigned to either the treatment group (n=10), which received MET combined with MWD, or the control group (n=10), which received Infrared (IR) and Transcutaneous Electrical Nerve Stimulation (TENS). Paired sample t-test results showed a statistically significant reduction in pain in both groups (p = 0.000). However, the independent sample t-test indicated a significant difference between groups (p = 0.001), with the treatment group demonstrating a greater mean reduction in pain (3.870) compared to the control group (2.290). In conclusion, the combination of MET and MWD was found to be more effective in reducing pain associated with NSLBP than conventional IR and TENS therapy.